The adipo‐fibrokine activin A is associated with metabolic abnormalities and left ventricular diastolic dysfunction in obese patients. (6th February 2019) - Zeller, Judith; Krüger, Carolin; Lamounier‐Zepter, Valeria; Sag, Sabine; Strack, Christina; Mohr, Margareta; Loew, Thomas; Schmitz, Gerd; Maier, Lars; Fischer, Marcus; Baessler, Andrea
Abstract: Aims: Left ventricular diastolic dysfunction (LVDD) is common in obese subjects, and a relationship between epicardial adipose tissue (EAT), increased adipocytokines, and cardiovascular diseases has been reported. This study sought to examine as to whether the adipo‐fibrokine activin A is a link between increased EAT, the metabolic syndrome (MetS), and LVDD in severely obese subjects. Methods and results: In 236 obese subjects (ø body mass index 39.8 ± 7.9 kg/m 2 ) with a variable degree of the MetS and in 60 healthy non‐obese controls (ø body mass index 24.8 ± 3.4 kg/m 2 ), serum activin A levels were measured and correlated with parameters of the MetS, epicardial fat thickness (EFT), and echocardiographic parameters of LVDD. Activin A levels were higher in obese than in non‐obese subjects (362 ± 124 vs. 301 ± 94 pg/mL, P = 0.0004), increased with the number of MetS components (from 285 ± 82 with no MetS component, 323 ± 94 with one or two MetS components, to 403 ± 131 pg/mL with ≥3 MetS components, P < 0.0001) and correlated with EFT ( r = 0.41, P < 0.001). Furthermore, activin A levels were related to several parameters of LVDD [e.g. left atrial size (382 ± 117 vs. 352 125 pg/mL, P = 0.024), E/e′ (394 ± 108 vs. 356 ± 127 pg/mL, P = 0.005)]. LVDD was highest in MetS obese subjects with high EFT (44.3%) compared with MetS obese subjects with low EFT (27.0%), non‐MetS obese subjects with high EFT (24.2%), and non‐MetS obese subjects with low EFT (10.6%, P < 0.0001). Conclusions: In severe obesity, activin A was significantly related to EFT, MetS, and LVDD, implicating MetS‐related alterations in the secretory profile of EAT in the pathogenesis of obesity‐related heart disease.